PENYULUHAN PENGGUNAAN LAMPU OTOMATIS BAGI MASYARAKAT - Simon Patabang; Jeremias Leda (Batara Wisnu : Indonesian Journal of Community Services, 2021)
The need for electrical energy for lighting for the community is an important thing. However, people tend to pay less attention to the savings in the use of electrical energy for lighting in the house, both at night and during the day. When leaving the house empty, in general, the porch light is on all day and night. This is a common thing for the community, but they unconsciously waste the use of electrical energy which will cause an increase in electricity bill bills. To increase knowledge for the community about the importance of saving electrical energy, in this community service counselling will be carried out on saving electrical energy by using automatic, energy-saving lamps. Counselling is done by visiting people's homes to explain the benefits of saving electricity for them. Then distribute and install energy-saving lamps with light sensors. With this service, the community has been able to understand well the benefits of saving electrical energy for them. The use of energy-saving lamps with light sensors can help people to save on the use of electrical energy. With this counselling, the community can save electrical energy for lighting, where the porch light will turn on automatically in the afternoon and will turn off automatically in the morning